Antithrombotic strategies in elderly patients with atrial fibrillation revascularized with drug-eluting stents: PACO-PCI (EPIC-15) registry. (14th October 2021) - De La Torre Hernandez, J M; Ferreiro, J L; Lopez Palop, R; Ojeda, S; Marti, D; Avanzas, P; Linares, J A; Diego, A; Amat, I J; Telleria, M; Cid, B; Otaegui, I; et al.
Abstract: Background: The strategy of antithrombotic therapy in patients with atrial fibrillation (AF) after revascularization with drug-eluting stents continues to be debated. The evidence in elderly population in this scenario is particularly scarce. Purpose: We sought to investigate the antithrombotic regimens applied and their prognostic effects in patients over 75 years old with AF after revascularization with drug-eluting stents. Methods: Retrospective registry in 20 centers including consecutive patients over 75 years with AF treated with drug-eluting stents. A primary endpoint of MACCE and a co-primary endpoint of major bleeding by ISTH criteria were considered at 12 months. Results: Out of 41, 000 patients undergoing PCI 1, 249 patients (81.1±4.2 years, 33.1% women, 66.6% ACS, 30.6% complex PCI) were included. Triple antithrombotic therapy (TAT) was prescribed in 81.7% and dual antithrombotic therapy (DAT) in 18.3%. TAT was based on direct oral anticoagulants (DOAC) in 48.4% and maintained for only 1 month in 52.2%, and DAT included DOAC in 70.6%. Primary endpoint of MACCE was met in 9.6% and primary endpoint of major bleeding in 9.4%. TAT was significantly associated with more bleeding (10.2% vs. 6.1%, p=0.04) but less MACCE (8.7% vs. 13.6%, p=0.02) than DAT and the use of DOAC was significantly associated to less bleeding (8% vs. 11.1%, p=0.03) and similar MACCE (9.8% vs. 9.4%, p=0.8). TAT over 1 month or with VKA was associated with more major bleeding but comparable MACCE rates. Conclusions: Despite advanced age TAT prevails, but prolonged durations or use of VKA are associated with increased bleeding without additional MACCE prevention. DAT reduces bleeding but with a trade-off in terms of ischemic events. DOAC use was significantly associated to less bleeding and similar MACCE rates. FUNDunding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Bristol-Myers-Squibb/Pfizer